Chemical Composition and Antimicrobial Activity of Ruta chalepensis L. Essential Oil from Algeria - MERGHACHE, S.; HAMZA, M.; BENDAHOU, M.; TABTI, B. (Asian Journal of Chemistry, 2010)
The essential oil from aerial parts of Ruta chalepensis L. was analyzed by GC and GC/MS. 20 Compounds were identified representing 93.99-98.58 % of the oil. 2-Undecanone (79.06- 82.74 %) was the major constituent, followed by 2-decanone (3.53 - 4.38 %). Variation in essential oil composition, physicochemical properties and yields was studied according to state of material used (fresh or dry) and years of collection of the plant. The essential oil of aerial parts was tested for its antimicrobial activity using paper disc diffusion method. The oil was ineffective on the inactivation of Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Listeria monocytogens. In the contrast the essential oil demonstrated significantly antifungal activities against Aspergillus niger, Aspergillus flavus, Alternaria Sp., Trichoderma Sp. and Candida albicans.